Strategi Pengawasan Konten Digital dalam Melindungi Anak dari Paparan Konten Berbahaya di Media Sosial: Penelitian - Nainggolang, Deklay; Tangkulung, Kanaya Isanasrania; Siregar, Lialis Marsity Br; Lampa, Zefanya Lintin (Lembaga Penelitian dan Pengabdian Masyarakat, 2026)
This study explores a range of strategies used to oversee digital content with the aim of protecting children from harmful material circulating widely on social media platforms. Using a mixed-method approach with a sequential explanatory model, this research integrates qualitative findings from literature studies with quantitative data obtained through surveys. The results indicate that effective protection for children in the digital environment requires a comprehensive combination of digital literacy education, active parental supervision, the utilization of technological safety tools such as parental control, open communication between parents and children, and supportive regulations enforced by digital service providers. This study concludes that collaboration among families, educational institutions, communities, and government authorities is essential for creating a safe digital ecosystem for children.